Crop-weed interactions and management in sesame: Current status and future challenges: WEED INTERACTIONS AND MANAGEMENT IN SESAME: CURRENT STATUS AND FUTURE CHALLENGES - ANKELA CHARAN BABU; K RAMESH; C HARISUDAN; KARETI HARIKA; RATNA KUMAR PASALA; G SURESH; DEVIKA SHAJY (Journal of Oilseeds Research, 2026)
Sesame is an important oilseed crop in India, predominantly cultivated under rainfed and low input conditions. Its productivity is severely constrained by weed infestation, particularly due to slow initial growth and poor canopy development, leading to yield losses of 50-75%. Under rainfed conditions, weed competition is particularly severe because weeds compete directly with the crop for limited soil moisture during the early growth stages. A wide range of weed management practices, including cultural, mechanical, biological, and chemical approaches have been reviewed. Cultural practices such as optimum sowing (time and method), mulching, intercropping, and seed priming enhance crop competitiveness, while mechanical methods such as hand weeding, inter-cultivation remain effective but labour intensive. Chemical control through pre-emergence herbicides, such as pendimethalin, alachlor, pendimethalin + imazethapyr and pyroxasulfone, and ACCase inhibitors such as quizalofop, fenoxaprop, propaquizafop, clethodim and haloxyfop as post-emergence options, provides efficient weed control. However, limitations such as phytotoxicity are reported with certain herbicides, including metribuzin, imazethapyr, diuron, and anilides at higher doses. Although sequential application of pre and post emergence herbicides ensures season long weed control, challenges such as limited post-emergence options for broad-leaved weeds and sedges and inadequate research focus persist. Integrated weed management, particularly the use of pre-emergence herbicides followed by timely hand weeding or intercultivation, has emerged as the most effective and sustainable approach. Recent advances in genetic variability and herbicide tolerance in sesame further open new avenues for improving weed management. Overall, integration of conventional and emerging approaches is essential for achieving sustainable and economically viable weed control in sesame.